A knowledge-based development model for primate cities of the developing world. (2018) - Hector, Paul G.C.; Ermine, Jean-Louis; Ribiere, Vincent; Bennet, Alex
This paper presents the conceptual development and piloting of a knowledge-based development model for primate cities. Using UNESCO's knowledge societies conceptual framework, the study extends this framework by substantiating relationships between the framework's components, intellectual capital, knowledge processes and macro-level sustainable development goals (economic, environmental, social as well as peace/security dimensions). An international Delphi panel of experts in the fields of knowledge management, knowledge cities and urban planning, validated the knowledge-based development model derived from the framework. Empirical field pilots were conducted with the model in primate cities in Ethiopia and Thailand to assess the relevance of the model and to explore what insights and guidance it could provide policy-makers. The model identified key resources and critical areas where policy interventions are needed. Feedback from respondents contributed to the model's improvement. A K-SWOT policy dialogue further demonstrated the model's potential for supporting decision-making.